2018
DOI: 10.1186/s12890-017-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to timely diagnosis of interstitial lung disease in the real world: the INTENSITY survey

Abstract: BackgroundThe diagnosis of idiopathic pulmonary fibrosis (IPF) and other interstitial lung diseases (ILD) presents significant clinical challenges. To gain insights regarding the diagnostic experience of patients with ILD and to identify potential barriers to a timely and accurate diagnosis, we developed an online questionnaire and conducted a national survey of adults with a self-reported diagnosis of ILD.MethodsA pre-specified total of 600 subjects were recruited to participate in a 40-question online survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 21 publications
8
144
2
3
Order By: Relevance
“…A majority of patients report waiting more than 1 year from the time of symptom onset to ILD diagnosis and often undergo multiple physician evaluations before arriving at the correct diagnosis [4]. Even with recognition of this problem, little headway has been made over the last decade [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of patients report waiting more than 1 year from the time of symptom onset to ILD diagnosis and often undergo multiple physician evaluations before arriving at the correct diagnosis [4]. Even with recognition of this problem, little headway has been made over the last decade [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date characterizing diagnostic delays in patients with ILD have largely relied on patient questionnaires and insurance claims data [4][5][6][7]. While informative, these studies do not assess physician-level factors that may influence such delays.…”
Section: Introductionmentioning
confidence: 99%
“…This disease represents a growing problem in the world and is the second most common respiratory disease in the United States 3,4 Other worldwide severe respiratory diseases are cystic fibrosis and interstitial lung disease. [5][6][7][8] Some diseases are congenital, such as cystic fibrosis, whereas others can be acquired through smoking, such as COPD. 9,10 Lung transplantation is an established intervention for patients with advanced and life-threatening respiratory disease for which standard medical treatment is no longer effective or for which there is no effective standard medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…AIP is a type of idiopathic interstitial pneumonia, whose pathogenesis remains unclear [22]. In addition, the diagnosis of idiopathic pulmonary fibrosis (IPF) and other ILD has been confronted with enormous clinical challenges [23]. It has been reported that pulmonary fibrosis usually manifests itself as a fibro-proliferative lung disease with an irreversible chronic progression and dismal prognosis [24].…”
Section: Discussionmentioning
confidence: 99%